2012
DOI: 10.3382/ps.2011-01873
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol as a contaminant of broiler feed: Effects on bird performance and response to common vaccines

Abstract: Recent data suggest that Fusarium trichothecenes may reduce broiler performance at levels previously thought not to affect this variable in chickens. In the present study, we investigated the effects of deoxynivalenol (DON), a type-B trichothecene, on broilers. Male broilers at 7 d of age were fed either a basal diet (0.265 ± 0.048 mg of DON; 0.013 ± 0.001 mg of zearalenone/kg), a low DON diet (1.68 mg of DON/kg; 0.145 ± 0.007 mg of zearalenone/kg), or a high DON diet (12.209 ± 1.149 mg of DON/kg; 1.094 ± 0.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 31 publications
1
61
0
1
Order By: Relevance
“…In contrast to swine, mycotoxins produced by Fusarium species, such as deoxynivalenol (DON) and fumonisins (FB), have not been considered as a major threat in poultry production, as more than 15 mg DON/kg and 80–100 mg FB/kg of diet are required to reduce performance in chickens [28,29,30]. However, as pointed out by Yunus et al [31], recent reports showed temporary reduction in broiler performance exposed to lower doses of DON (also shown for aflatoxins). The modern broiler has a faster growth rate that can affect the relative sensitivity of birds to mycotoxins in comparison to traditional broiler prior to the 2000s.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to swine, mycotoxins produced by Fusarium species, such as deoxynivalenol (DON) and fumonisins (FB), have not been considered as a major threat in poultry production, as more than 15 mg DON/kg and 80–100 mg FB/kg of diet are required to reduce performance in chickens [28,29,30]. However, as pointed out by Yunus et al [31], recent reports showed temporary reduction in broiler performance exposed to lower doses of DON (also shown for aflatoxins). The modern broiler has a faster growth rate that can affect the relative sensitivity of birds to mycotoxins in comparison to traditional broiler prior to the 2000s.…”
Section: Discussionmentioning
confidence: 99%
“…In broiler chickens, DON was shown to suppress the vaccination response to infectious bronchitis virus (IBV) [6] and to Newcastle disease virus (NDV) [6], [7]. Recently, DON was shown to suppress the antibody response to infectious bronchitis vaccine (IBV) in broiler chickens [8], [9]. Furthermore, it was shown that the dietary inclusion of DON in diets of laying hens resulted in a reduction of white blood cell number and total lymphocyte number [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although DON mycotoxicosis is rarely happened in modern poultry industry, moderate and low DON contamination of chicken diets reduced the production and impaired the health and immunological functions [9], [36]. In chickens, DON was shown to suppress the vaccination response to infectious bronchitis virus (IBV) [2], [11], [12] and to Newcastle disease virus (NDV) [2] which indicates that DON altered the chicken humoral immunity. It was shown that DON induces chronic stress in broiler chickens as measured by H/L ratio (Stress index) due to prolonged ingestion [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence to prolonged stress, the immune system of the birds can be affected [42]. In this respect, DON was shown to affect the humoral immune response to common vaccines [11], [12]. Indeed, the innate immune response is also altered due to chronic DON feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation